Embodied and Embedded Theory in Practice: The Student-Owned Learning-Engagement (SOLE) Model - Atkinson, Simon (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2011)
The demands on academic staff in all sectors to adopt best ODL practices to create effective and efficient models of learning in the face of increasing external pressures show no signs of abating. The massification of higher education, diversified access, and pressures to meet institutional visions and research objectives demand of teaching staff an increasingly public design process subject to peer review in numerous forms. Expectations of systematized pedagogical planners and embedded templates of learning within the institutional virtual learning environments (VLEs) have, so far, failed to deliver the institutional efficiencies anticipated. In response, a new model of learning design is proposed with a practical, accessible, and freely available toolkit that embodies and embeds pedagogical theories and practices. The student-owned learning-engagement (SOLE) model aims to support professional development within practice, constructive alignment, and holistic visualisations, as well as enable the sharing of learning design processes with the learners themselves.